Virus-like particles : a comprehensive guide - Pumpens, Paul; Pushko, Peter (London: CRC Press, 2022)
"This book represents the first complete and systematic guide to the virus-like particles (VLPs) and their applications as vaccines, therapeutic tools, nanomaterials, and nanodevices. The grouping of the VLPs follows the most recent virus taxonomy and the traditional Baltimore classification of viruses, which are based on the genome structure and mechanism of mRNA synthesis. Within each of the seven Baltimore classes, the order taxon serves as a framework of the chapter's arrangement. The term "VLP" is used as a universal designation for the virus-, core-, or capsid-like structures, which became an important part of the modern molecular virology. The 3D structures, expression systems, and nanotechnological applications are described for VLPs in the context of the original viruses and uncover their evolving potential as novel vaccines and medical interventions"--
Order Caudovirales -- Order Herpesvirales -- Order Asfuvirales -- Order Rowavirales -- Other double-stranded DNA viruses -- Order Lefavirales -- Order Zurhausenvirales -- Order Sepolyvirales -- Order Piccovirales -- Order Cirlivirales -- Order Tubulavirales -- Other single-stranded DNA viruses -- Order Reovirales -- Family Birnaviridae -- Other double-stranded RNA viruses -- Order Hepelivirales -- Order Martellivirales: Bromoviridae -- Order Martellivirales : Togaviridae -- Order Martellivirales : Virgaviridae -- Order Martellivirales : Other Families -- Order Tymovirales -- Order Amarillovirales -- Order Nodamuvirales -- Order Tolivirales -- Orders Norzivirales and Timlovirales -- Order Nidovirales -- Order Sobelivirales -- Order Patatavirales -- Other positive single-stranded RNA viruses -- Order Mononegavirales -- Order Bunyavirales -- Order Articulavirales -- Other negative single-stranded RNA viruses -- Order Ortervirales -- Family Caulimoviridae -- Order Blubervirales: Surface Protein -- Order Blubervirales: Core Protein.
Includes bibliographical references and indexes.
Keywords: Viral Structural Proteins; Viral Structural Proteins; Vaccines, Virus-Like Particle